2017
DOI: 10.1155/2017/4627384
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NK Cells in Pig-to-Human Xenotransplantation

Abstract: Recruitment of human NK cells to porcine tissues has been demonstrated in pig organs perfused ex vivo with human blood in the early 1990s. Subsequently, the molecular mechanisms leading to adhesion and cytotoxicity in human NK cell-porcine endothelial cell (pEC) interactions have been elucidated in vitro to identify targets for therapeutic interventions. Specific molecular strategies to overcome human anti-pig NK cell responses include (1) blocking of the molecular events leading to recruitment (chemotaxis, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 183 publications
0
27
0
Order By: Relevance
“…To test this, we compared the activity of human NK cells triggered by pFb from B2M low and wt pigs. We found no difference in the responsiveness of NK cells to the 2 stimulator cell types (Figure B), which supports earlier findings suggesting that SLA class I is not an inhibitory ligand for human NK cells and that NK‐mediated killing of porcine cells is MHC independent . Sequence comparison between porcine and human MHC class I molecules revealed that the binding regions responsible for interaction with NK cells differ between the 2 species…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we compared the activity of human NK cells triggered by pFb from B2M low and wt pigs. We found no difference in the responsiveness of NK cells to the 2 stimulator cell types (Figure B), which supports earlier findings suggesting that SLA class I is not an inhibitory ligand for human NK cells and that NK‐mediated killing of porcine cells is MHC independent . Sequence comparison between porcine and human MHC class I molecules revealed that the binding regions responsible for interaction with NK cells differ between the 2 species…”
Section: Discussionmentioning
confidence: 99%
“…Expression of human CD39 and CD73 and deletion of porcine von Willebrand factor (vWF) may further reduce platelet aggregation and deposition on NPIs, while various human coagulation regulatory proteins, including EPCR, TM, and TFPI, may inhibit downstream clotting . Lastly, expression of human HLA‐E and CD47 on NPIs reduces NK and macrophage infiltration . Although germline genetic modifications are generally required in solid organ xenotransplantation, genetic modifications may also be achieved temporarily in NPIs via viral vectors .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, pluripotent stem cells overexpressing HLA‐E were less detected by NK cells and allogeneic T cells (Gornalusse et al, ). It is now well understood that early rejection of pig to human xenografts occurs as a result of host NK cell activation (Puga Yung, Schneider, & Seebach, ). The pig MHC‐I (SLA‐I) molecules weakly interact with inhibitory receptors of human NK cells resulting in a just mild inhibition.…”
Section: Introductionmentioning
confidence: 99%